Molecular detection of Brucella canis in Blood of Dogs - Hussain Fawzi Saud; Taha Yassin Ghani (Indian Journal of Forensic Medicine & Toxicology, 2022)
The aims of this study was to evaluate a PCR for detecting Brucella canis in the blood of dogs, using aprimer pair designed for Brucella spp.A study was conducted on 150 blood sample collected from dogs suspected to Veterinary Hospitalin Baghdad / Aden Square. All blood samples (150) were tested by PCR technique using a commonprimer of the 23S ribosomal RNA (23s RNA) gene and specific primer for brucella canis (B0548).The genomic DNA was extracted and PCR was applied. Our study recorded 5.3% of brucellosis incommon primer and 3.3% in specific primer for brucella canis in dog in Baghdad city, the sequencesof Brucella canis in dog in different isolates in our study recorded 99% compatibility recording toNational Center Biotechnology Information (NCBI). Following correspondence from National Centerfor Biotechnology Information, the 23S ribosomal RNA gene was registered, given an agreementnumber, and became a resource for Iraq and Middle East, as well as the rest of the world. As more typestrains are published, this set will grow, and it can be download from NCBI at: https://www.ncbi.nlm.nih.gov/nuccore/.From this study we can conclude that, the percentage of Brucellosis in dogs in Baghdad city is 5.3% and3.3% in a common and specific primer, respectively and the molecular method (PCR), is a good ideafor confirmation of diagnosis of Brucella canis infection in dog.